2009
DOI: 10.5194/bgd-6-5589-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air-sea CO<sub>2</sub> fluxes in the Atlantic as measured during the FICARAM cruises

Abstract: Abstract. A total of fourteen hydrographic cruises spanning from 2000 to 2008 were conducted during the spring and autumn seasons between Spain and the Southern Ocean, under the framework of the Spanish research project FICARAM. The performed underway measurements are processed and analysed to describe the meridional air-sea CO2 fluxes (FCO2) along the Atlantic Ocean. The data was organised into different biogeochemical oceanographic provinces, according mainly to the thermohaline characteristics. The obtained… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Further north, lower sea surface salinities are observed in the North Equatorial Counter Current (NECC) that develops between approximately 2 • N and 10 • N. The climatology of Takahashi et al (2009) shows an fCO 2 gradient between these two current systems with higher values south of 2 • N and lower values in the NECC region but, on average, seawater fCO 2 is above the atmospheric level. This North-South gradient was also recently observed by Padin et al (2009) who reported near-equilibrium conditions between 1 • N and 8 • N around 28 • W during their FICARAM cruises while CO 2 supersaturation occurred further south between 1 • N and 15 • S. A few cruises have reported CO 2 concentrations below the atmospheric level in the north western tropical Atlantic and the origin of the CO 2 undersaturation was attributed to the discharge of the Amazon outflow (Ternon et al, 2000;Körtzinger, 2003). The Amazon is the largest river in the world representing about 20% of river supply to the world ocean, with a flow of 0.2 Sv (1 Sv = 10 6 m 3 s −1 ).…”
Section: Introductionsupporting
confidence: 82%
“…Further north, lower sea surface salinities are observed in the North Equatorial Counter Current (NECC) that develops between approximately 2 • N and 10 • N. The climatology of Takahashi et al (2009) shows an fCO 2 gradient between these two current systems with higher values south of 2 • N and lower values in the NECC region but, on average, seawater fCO 2 is above the atmospheric level. This North-South gradient was also recently observed by Padin et al (2009) who reported near-equilibrium conditions between 1 • N and 8 • N around 28 • W during their FICARAM cruises while CO 2 supersaturation occurred further south between 1 • N and 15 • S. A few cruises have reported CO 2 concentrations below the atmospheric level in the north western tropical Atlantic and the origin of the CO 2 undersaturation was attributed to the discharge of the Amazon outflow (Ternon et al, 2000;Körtzinger, 2003). The Amazon is the largest river in the world representing about 20% of river supply to the world ocean, with a flow of 0.2 Sv (1 Sv = 10 6 m 3 s −1 ).…”
Section: Introductionsupporting
confidence: 82%
“…In the tropical Atlantic, the variability of fCO 2 is affected by salinity changes [ Oudot et al ., ], and low fCO 2 values have been observed in the region of the NECC where high precipitation occurs because of the presence of the ITCZ [ Lefèvre et al ., ; Oudot et al ., ; Padin et al ., ]. This mechanism has also been observed in the equatorial Pacific [ Turk et al ., ] and is due to the chemical dilution taking place in these regions.…”
Section: Fco2 Sst and Sss Variability Along The Ship Trackmentioning
confidence: 53%